A two-center retrospective study: association of early caffeine administration and oxygen radical diseases in neonatology in Chinese preterm neonates - Ye, Huiqing; Bai, Liyang; Yang, Manting; Yang, Xiaoyuan; Zheng, Maofei; Zhong, Xiaobing; Yang, Lifen; Chen, Zhuanggui; Zhong, Xinqi (Frontiers in Pediatrics, 2023)
Introduction Since December 2012, the prophylactic use of caffeine to treat AOP in preterm infants has been approved in China. This study aimed to investigate the relationship between early caffeine treatment initiation and the incidence of oxygen radical diseases in neonatology (ORDIN) in Chinese preterm infants. Methods A retrospective study was conducted at two hospitals in South China, involving 452 preterm infants with gestational ages less than 37 weeks. The infants were divided into early (227 cases, initiating within 48 h after birth) and late (225 cases, initiating over 48 h after birth) caffeine treatment group. Logistic regression analysis and Receiver Operating Characteristic (ROC) curves were used to evaluate the association between early caffeine treatment and the incidence of ORDIN. Results The results showed that extremely preterm infants in early treatment group had a lower incidence of PIVH and ROP compared to those in the late treatment group (PIVH, 20.1% versus 47.8%, P = 0.02; ROP, 70.8% versus 89.9%, P = 0.025). Very preterm infants in the early treatment group had a lower incidence of BPD and PIVH compared to those in the late treatment group (BPD, 43.8% versus 63.1%, P = 0.002; PIVH, 9.0% versus 22.3%, P = 0.001). Moreover, VLBW infants who received early caffeine treatment exhibited a decreased incidence of BPD (55.9% versus 80.9%, P = 0.000), PIVH (11.8% versus 33.1%, P = 0.000), and ROP (69.9% versus 79.8%, P = 0.043) compared to those in the late treatment group. Infants in the early caffeine treatment showed a reduced likelihood of PIVH (adjusted odds ratio, 0.407; 95%CI, 0.188–0.846) but did not exhibit a significant association with other terms of ORDIN. ROC analysis revealed that early initiation of caffeine treatment was associated with lower risk of BPD, PIVH, and ROP in preterm infants. Discussion In conclusion, this study demonstrates that early initiation of caffeine treatment is associated with a decreased incidence of PIVH in Chinese preterm infants. Further prospective investigations are necessary to verify and elucidate the precise effects of early caffeine treatment on complications in preterm Chinese infants.